Vaginal Removal of Very Large Nascent Uterine Myoma – Case Report and Literature Review - Terzic, M.; Maricic, S.; Dotlic, J. (Geburtshilfe und Frauenheilkunde, 2013)
This report shows that even extremely large nascent uterine myomas can be removed vaginally. A 25-year-old nulligravid and nulliparous patient with malaise, hypermenorrhea, and intermittent cramping pain in the lower abdomen was referred to our clinic. Gynecological examination revealed a round cauliflower-like tumor, 7 cm in diameter, originating from the external cervical os with a rough surface and without a palpable stalk or base. Ultrasound scan showed a hyperechogenic mass within the uterine cavity with two distinct subunits: one (55 × 44 mm) well-demarcated from the surrounding structures and the other (43 × 38 mm) in close proximity to the lower part of the anterior uterine wall and in continuity with the myometrium. At surgery, the myoma was completely removed vaginally. Recovery was prompt, complete, and uneventful. Follow-up at one and three months confirmed normal gynecological and sonographic findings. In conclusion, vaginal myomectomy is the treatment of choice for prolapsed pedunculated submucous myoma; even extremely large nascent myomas can be efficiently removed vaginally.
Keywords: benign uterine tumor; nascent myoma; vaginal myomectomy